Design and optimization of a liquid cooled heat sink for a motor inverter in electric vehicles. (1st June 2021) - Han, Feng; Guo, Hong; Ding, Xiaofeng
Highlights: Integrated design of heat sink considering the layout of power devices was performed. Temperature distribution and fluid velocity filed of three heat sinks were analyzed. Effects of fin thickness and flow rate on temperature and pressure drop was studied. The accuracy of the numerical simulation results has been verified by the experiment. The motor inverter with the new configuration heat sink achieves high power density. Abstract: The rapid development of power electronic devices has made them have higher power density, which puts forward higher requirements for cooling technology. The contribution of this paper is the integrated design of the liquid cooled heat sink for a 30 kW motor inverter considering the distribution of power devices. In order to find an optimal heat sink configuration, the cooling performance of three different configurations of heat sinks was investigated. And the distribution characteristics of the temperature and fluid velocity field were compared and analyzed. The heat sink with serpentine channel configuration was selected due to its best temperature uniformity and cooling characteristic. In addition, the effects of geometric parameters (fin thickness) and flow parameters (flow rate) on cooling performance were further studied. On this basis, the geometrical configuration of the heat sink was optimized. The experimental results of the optimized heat sink are in good agreement with the numerical simulation results. The motor inverter achieves high power density of 9.677 kW/kg.